2019
DOI: 10.3847/1538-4357/aaf646
|View full text |Cite
|
Sign up to set email alerts
|

How Initial Size Governs Core Collapse in Globular Clusters

Abstract: Globular clusters (GCs) in the Milky Way exhibit a well-observed bimodal distribution in core radii separating the so-called "core-collapsed" and "non-core-collapsed" clusters. Here, we use our Hénon-type Monte Carlo code, CMC, to explore initial cluster parameters that map into this bimodality. Remarkably, we find that by varying the initial size of clusters (specified in our initial conditions in terms of the initial virial radius, r v ) within a relatively narrow range consistent with the measured radii of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
115
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 111 publications
(124 citation statements)
references
References 102 publications
9
115
0
Order By: Relevance
“…Thus, by varying r v (here, from 0.5-4 pc) the full distribution of cluster core radii is naturally captured. This same result was demonstrated in Kremer et al (2019a) for a much smaller set of models of fixed particle number and metallicity. Here, we demonstrate this result for a much broader set of cluster properties.…”
Section: Comparison With the Milky Way Cluster Populationsupporting
confidence: 78%
See 4 more Smart Citations
“…Thus, by varying r v (here, from 0.5-4 pc) the full distribution of cluster core radii is naturally captured. This same result was demonstrated in Kremer et al (2019a) for a much smaller set of models of fixed particle number and metallicity. Here, we demonstrate this result for a much broader set of cluster properties.…”
Section: Comparison With the Milky Way Cluster Populationsupporting
confidence: 78%
“…Much of the recent theoretical work on GC dynamics has focused on the crucial role played by stellar black hole (BH) remnants in these systems. Several studies have shown that large numbers of stellar-mass BHs can be retained in typical GCs all the way to the present, and their dynamical interactions in the cluster core over its ∼ 12 Gyr of evolution provide a natural physical explanation for many of the diverse cluster features alluded arXiv:1911.00018v1 [astro-ph.HE] 31 Oct 2019 to in the previous paragraph (e.g., Morscher et al 2015;Mackey et al 2008;Breen & Heggie 2013;Askar et al 2018;Kremer et al 2019a). The first BH candidate in a cluster was identified in the extragalactic GC NGC 4472 by Maccarone et al (2007) through X-ray observations.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations